Prevalence and associated factors of depression and anxiety among patients with cancer seeking treatment at the Butaro Cancer Center of Excellence in Rwanda - Habimana, Samuel; Biracyaza, Emmanuel; Mpunga, Tharcisse; Nsabimana, Epaphrodite; Kayitesi, Florence; Nzamwita, Pascal; Jansen, Stefan (Frontiers in Public Health, 2023)
Background Depression and anxiety are psychological and physiological disturbances persisting in cancer patients with high prevalence worldwide, particularly in low- and middle-income countries, due to complexities of determinants of health including biological, individual, socio-cultural, and treatment-related characteristics. Although depression and anxiety have an enormous impact on adherence, length of stay at the hospital, quality of life, and treatment outcomes, studies on psychiatric disorders remain limited. Thus, this study determined the prevalence and factors of depression and anxiety among patients with cancer in Rwanda. Methods A cross-sectional study was conducted among 425 patients with cancer from the Butaro Cancer Center of Excellence. We administered socio-demographic questionnaires and psychometric instruments. Bivariate logistic regressions were computed to identify significant factors to be exported into the multivariate logistic models. Then, odds ratios and their 95% confidence intervals were applied, and statistical significance at p < 0.05 were considered to confirm significant associations. Results The prevalence of depression and anxiety was 42.6 and 40.9%, respectively. Patients with cancer initiated to chemotherapy had a greater likelihood of being depressed [AOR = 2.06; 95% CI (1.11–3.79)] than those initiated to chemotherapy and counseling. Breast cancer was significantly associated with a greater risk of depression [AOR = 2.07, 95% CI (1.01–4.22)] than Hodgikins's Lymphoma cancer. Furthermore, patients with depression had greater odds of developing anxiety [AOR = 1.76, 95% CI (1.01–3.05)] than those with no depression. Those suffering from depression were almost two times more likely to experience anxiety [AOR = 1.76; 95% CI (1.01–3.05)] than their counterparts. Conclusion Our results revealed that depressive and anxious symptomatology is a health threat in clinical settings that requires enhancement of clinical monitoring and prioritization of mental health in cancer health facilities. Designing biopsychosocial interventions to address associated factors needs special attention to promote the health and wellbeing of patients with cancer.